Leviathan Inc. and corporate environmental engagement - HSU, Po-Hsuan (Institutional Knowledge at Singapore Management University, 2023)
In a 2010 special report, The Economist magazine termed the resurgence of state-owned, publicly listed enterprises “Leviathan Inc.” and criticized the poor governance and low efficiency of these firms. We compile a new comprehensive data set of state ownership of publicly listed firms in 44 countries over the period of 2004–2017 and show that state-owned enterprises are more responsive to environmental issues. The effect is more pronounced in economies lacking energy security and strong environmental regulation, and among firms with more local operations and higher domestic government ownership. We find a similar effect on corporate social engagement but not on governance quality. These results suggest a different role for “Leviathan Inc.,” especially in dealing with environmental externalities.